The Effect of Digital Capability and Market Orientation on Marketing Performance - Vera Selviana Adoe; Feba Dinova Dex Tovtora; Rini Hadiyati; Deni Adha Akbari; Dewi Rakhmawati (West Science Business and Management, 2026)
This study aims to examine the influence of digital competence and market orientation on marketing performance in Indonesia. In the era of rapid digital transformation, organizations are required to adapt their marketing strategies by utilizing digital technologies while maintaining a strong understanding of market dynamics. Digital competence enables organizations to effectively use digital platforms, analyze market data, and communicate with customers more efficiently, while market orientation emphasizes understanding customer needs, monitoring competitors, and responding to market changes. This research adopts a quantitative approach using a survey method involving 250 respondents engaged in marketing activities across various organizations in Indonesia. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using the Statistical Package for Social Sciences (SPSS) version 25, including descriptive statistics, validity and reliability testing, and multiple linear regression analysis to test the proposed hypotheses. The results indicate that digital competence has a positive and significant effect on marketing performance, and market orientation also shows a positive and significant influence on marketing performance. Simultaneous analysis further demonstrates that both variables significantly affect marketing performance with a coefficient of determination (R² = 0.549), indicating that 54.9% of the variation in marketing performance can be explained by digital competence and market orientation. These findings highlight the importance of strengthening digital capabilities and maintaining a strong market-oriented approach to improve marketing effectiveness. This study contributes to the marketing literature by providing empirical evidence on the role of digital competence and market orientation in enhancing marketing performance in Indonesia, and practically suggests that organizations should invest in developing digital skills while continuously monitoring market dynamics to remain competitive in the digital business environment.